2021
DOI: 10.3389/fnins.2021.696861
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Exerts Antinociceptive Effects in Cancer-Induced Bone Pain via an Endogenous Opioid Mechanism

Abstract: Cancer pain is one of the main complications in advanced cancer patients, and its management is still challenging. Therefore, there is an urgent need to develop novel pharmacotherapy for cancer pain. Several natural products have attracted the interest of researchers. In previous studies, curcumin has proved to exhibit antitumor, antiviral, antioxidant, anti-inflammatory, and analgesic effects. However, the analgesic mechanism of curcumin has not been elucidated. Thus, in this study, we aimed to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The results also indicate that the enhanced expression of DRG neuron β-endorphin and enkephalin contributes to curcumin’s pain-relieving effects in conditions characterized by heightened pain sensitivity. This is the first time that curcumin has been shown to have an antinociceptive effect in pain hypersensitivity conditions, and the effects may be mediated by increased expression of β-endorphin and enkephalin which was demonstrated by Zhao et al in 2021 [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results also indicate that the enhanced expression of DRG neuron β-endorphin and enkephalin contributes to curcumin’s pain-relieving effects in conditions characterized by heightened pain sensitivity. This is the first time that curcumin has been shown to have an antinociceptive effect in pain hypersensitivity conditions, and the effects may be mediated by increased expression of β-endorphin and enkephalin which was demonstrated by Zhao et al in 2021 [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin administration (cC and nC) also had an analgesic effect ( Figure 2 ). Its analgesic effect could be explained by the stimulation of protein expression of β-endorphin and encephalin, which are endogenous opioid peptides [ 18 ]. We observed that the association of cC and nC to D has better analgesic effects ( Figure 2 ), most probably because the combination acts on two mechanisms to reduce the pain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been known for its multiple therapeutic potentials, including its analgesic potentials. [11][12][13][14][15][16] As an analgesic agent, including in the orofacial region, curcumin has been evaluated and delivered in several forms, capsule, gel, paste, powder, as well as in a form of a patch. 17,18 A previous study revealed that transdermal delivery of an analgesic agent, will eliminate unwanted side effects such as sedation and cognition.…”
Section: Introductionmentioning
confidence: 99%